Efficacy and safety of BTK inhibitors in Richter’s transformation: a systematic review of clinical evidence - Dirican, Canan D.; Ajayi, Folasade; Al Mardini, Anas; Crocete Aloysia Fernandes, Bolivia; Sofia, Amara; Gondhi, Venkatesh; Shaaban, Hamid; Maroules, Michael (Frontiers in Oncology, 2026)
BackgroundRichter’s transformation (RT) is an aggressive progression of chronic lymphocytic leukemia (CLL) or small lymphocytic lymphoma (SLL), most commonly to diffuse large B-cell lymphoma (DLBCL). Therapeutic options are limited, and outcomes are poor, particularly in relapsed or refractory cases. Bruton’s tyrosine kinase (BTK) inhibitors have transformed the treatment landscape of CLL, but their role in RT is less well defined.MethodsWe conducted a systematic review in accordance with PRISMA guidelines to evaluate the efficacy and safety of BTK inhibitor–based therapies in patients with RT. PubMed, EMBASE, and ClinicalTrials.gov were searched through January 1, 2025. Clinical trials reporting outcomes such as overall response rate (ORR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs) in RT patients treated with BTK inhibitors were included.ResultsSeven studies (six clinical trials and one case series) comprising 220 patients were included. Monotherapy with pirtobrutinib and acalabrutinib showed ORRs of 50% and 40%, respectively. Combination regimens such as zanubrutinib plus tislelizumab and ibrutinib plus nivolumab demonstrated ORRs ranging from 41.6% to 65%, with improved outcomes in treatment-naïve patients. Safety profiles were generally manageable, though grade ≥3 AEs, particularly cytopenias and infections, were common. Risk of bias was moderate to serious across studies due to non-randomized designs and small sample sizes.ConclusionBTK inhibitor–based therapies show promising efficacy in patients with RT, particularly in combination with immunotherapeutic agents. While monotherapy may offer a tolerable option for frail patients, combination regimens may improve outcomes in select populations. Larger, randomized controlled trials are needed to better define the role of BTK inhibition in this high-risk disease.